2014
DOI: 10.3126/narj.v8i0.11608
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Disorders and Seroprevalence of Brucellosis in Yak

Abstract: A study on reproductive disorders among yaks in Mustang and Solukhumbu districts and seroprevalence of brucellosis among yaks in Mustang and Myagdi districts was conducted. Eleven farmers having 383 female and 72 male yaks in Mustang and 129 female and 27 male yaks in Solukhumbu districts were taken by purposive random sampling for the study on reproductive disorders. Likewise Sixty-seven serum samples were also collected from adult female yaks having history of abortion and retained placenta, and from male ya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…In this study the seroprevalence of brucellosis in pregnant women was found to be 11.25%. Previously, it was reported that the seroprevalence of human brucellosis in Kathmandu was 11.95% [12]. Similarly, it was reported as 20% in Surkhet district and 14% in the patients visiting Bir hospital [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study the seroprevalence of brucellosis in pregnant women was found to be 11.25%. Previously, it was reported that the seroprevalence of human brucellosis in Kathmandu was 11.95% [12]. Similarly, it was reported as 20% in Surkhet district and 14% in the patients visiting Bir hospital [13].…”
Section: Discussionmentioning
confidence: 99%
“…The seroprevalence of brucellosis was high (2.72%) among the people above 50 years age group in Chitwan [16], 20-29 years (29%) in Surkhet [13] and 6-15 years age group (29.17% ) in Kathmandu [12].…”
Section: Discussionmentioning
confidence: 99%
“…Although brucellosis has been reported to be endemic in Nepal, neither the distribution nor the economic and public health impact of this disease is well characterized [ 44 , 46 ]. Robust and well-designed nationwide survey is warranted to assess the prevalence and distribution of disease in livestock and humans.…”
Section: Main Bodymentioning
confidence: 99%
“…Although there are some published studies describing the seroprevalence of animal and human brucellosis in Nepal [24][25][26], there are no studies that describe the risk factors related to animal brucellosis in Nepal. Identifying risk factors and implementing prevention and control programs could lead to a decrease in the disease burden in small ruminants, with consequent improvements in human health.…”
Section: Introductionmentioning
confidence: 99%